At‐home sperm testing for epidemiologic studies: Evaluation of the Trak male fertility testing system in an internet‐based preconception cohort. Issue 5 (15th December 2019) - Sommer, Greg J.; Wang, Tanran R.; Epperson, Jon G.; Hatch, Elizabeth E.; Wesselink, Amelia K.; Rothman, Kenneth J.; Fredriksen, Laura L.; Schaff, Ulrich Y.; Behr, Barry; Eisenberg, Michael L.; Wise, Lauren A.
Abstract: Background: Semen quality assessment in population‐based epidemiologic studies presents logistical and financial challenges due to reliance on centralised laboratory semen analysis. The Trak Male Fertility Testing System is an FDA‐cleared and validated at‐home test for sperm concentration and semen volume, with a research use only sperm motility test. Here we evaluate the Trak System's overall utility among men participating in Pregnancy Study Online (PRESTO), a web‐based study of North American couples planning pregnancy. Methods: US male participants aged ≥21 years with ≤6 months of pregnancy attempt time at study enrolment were invited to participate in the semen testing substudy after completing their baseline questionnaire. Consenting participants received a Trak Engine (battery‐powered centrifuge) and two test kits. Participants shared their test results via smartphone images uploaded to online questionnaires. Data were then linked with covariate data from the baseline questionnaire. Results: Of the 688 men invited to participate, 373 (54%) provided consent and 271 (73%) completed at least one semen test result. The distributions of semen volume, sperm concentration, motile sperm concentration, total sperm count, and total motile sperm count were similar to 2010 World Health Organization (WHO) semen parameter data of men in the general population. The overall usability score for the Trak System was 1.4 on a 5‐point Likert scale (1 = Very Easy, 5 = Difficult), and 92% of participants believed they performed the test correctly and received an accurate result. Lastly, men with higher motile sperm count were more likely to report feeling "at ease" or "excited" following testing, while men with low motile sperm count were more likely to report feeling "concerned" or "frustrated." Overall, 91% of men reported they would like to test again. Conclusions: The Trak System provides a simple and potentially cost‐effective means of measuring important semen parameters and may be useful in population‐based epidemiologic fertility studies.